Analisis Spasial Kota Palembang dengan Metode Space Syntax - Meldo Andi Jaya; Reny Kartika Sary; Muhammad Hijrah Agung Sarwandy; Iskandar Iskandar (Universitas Muhammadiyah Palembang, 2025)
Spatial characteristic of Palembang city influenced by Musi River which separates the region into two parts, Ulu and Ilir. the features of these part contrast. Comparing to the Ulu region, the Ilir region has denser and larger area. Historically, the Ilir region continues to be the center of governance and commerce from the Palembang Sultanate, the duch colonial empire, as long as the present. The research aims to measure the level of connectivity, integration, and choice of the spatial of Palembang city. Connectivity analysis, Global Integration, local integration, and choce were the methods adopted. Map-base data collected through Open Street Map (OSM), which is processed by QGis software then analized with Depthmap’s Space Syntax methods.